TACTICAL IMPORTANCE OF INVESTIGATIVE CUNNING IN THE INVESTIGATION OF CRIMES - PODOL'NYY Nikolai Alexandrovich (Правовое государство: теория и практика, 2022)
As a type of tactical techniques, investigative cunning is a means of establishing the circumstances of the crime committed. However, this type of tactical techniques is quite ambiguously accepted by both theory and practice of investigation. The purpose of the study, which is the basis of the proposed article, is to justify the tactical importance of investigative cunning, which allows using it to optimize the ongoing investigation. At the same time, a whole arsenal of scientific methods is used: analysis and synthesis, system-activity, situational modeling. They make it possible to study comprehensively the problems that arise in the investigation and can be removed using investigative cunning. The result of the study is the conclusion that investigative cunning is a tool that can increase the effectiveness of the investigation. At the same time, investigative cunning is the key to the investigator’s tactical victory against those who do not want to find out the truth in the case and make a fair procedural decision.